2020
DOI: 10.3390/ijerph17072517
|View full text |Cite
|
Sign up to set email alerts
|

What Accounts for Physical Activity during Pregnancy? A Study on the Sociodemographic Predictors of Self-Reported and Objectively Assessed Physical Activity during the 1st and 2nd Trimesters of Pregnancy

Abstract: Physical activity (PA) during pregnancy has positive health implications for both mother and child. However, current literature indicates that not all pregnant women meet the international recommendations for PA (at least 150 min/week of moderate-to-vigorous PA). The main objective of this study was to assess PA levels among pregnant women in the city of Donostia-San Sebastian and identify their main sociodemographic predictors. We recruited 441 women in the 12th week of pregnancy from the local public obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
(107 reference statements)
2
16
1
2
Order By: Relevance
“…While there are several studies to guide interventions and the promotion of physical activity and exercise among pregnant women in the USA [3,25,65,70,71], Canada [63,72,73], the United Kingdom [74][75][76] and other countries around the world [26,53,57,61,62,68,[77][78][79][80][81][82][83], which indicate varying degrees of PA participation, and suggest the reasons for both participation and non-participation during pregnancy, scant information exist in Africa. A previous review by Mukona et al [84] identified only two studies conducted in South Africa [56,85], two studies in Nigeria [86,87], and one study in Ethiopia [88].…”
Section: Introductionmentioning
confidence: 99%
“…While there are several studies to guide interventions and the promotion of physical activity and exercise among pregnant women in the USA [3,25,65,70,71], Canada [63,72,73], the United Kingdom [74][75][76] and other countries around the world [26,53,57,61,62,68,[77][78][79][80][81][82][83], which indicate varying degrees of PA participation, and suggest the reasons for both participation and non-participation during pregnancy, scant information exist in Africa. A previous review by Mukona et al [84] identified only two studies conducted in South Africa [56,85], two studies in Nigeria [86,87], and one study in Ethiopia [88].…”
Section: Introductionmentioning
confidence: 99%
“…The study of mediator variables reveals that participants experienced low-to-moderate levels of psychological stress and exercised, on average, above the international PA recommendations. With regard to NO 2 , average concentration values in the study area (mean = 46.7 µg/m 3 ; SD = 22.36) were higher than the average annual value in the Basque Country (mean = 22-30µg/m 3 ) [71]. In relation to outcome variables, 9.3, 14.6, 4.8, and 3.3% of the births were categorized as SGA, LGA, LBW, or premature, respectively.…”
Section: Testing the Multiple Pathways Of Residential Greenness To Pregnancy Outcomes Model In The Study Samplementioning
confidence: 55%
“…Around two-thirds of the sample had completed tertiary education (64.60%) and were working at the time of data collection (79.94%). The sociodemographic profile of the study participants and further data on their characteristics can be found elsewhere [71].…”
Section: Testing the Multiple Pathways Of Residential Greenness To Pregnancy Outcomes Model In The Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the substantial evidence on the benefits of PA during pregnancy, studies have reported a considerable decline in PA among pregnant women in both developed [47][48][49][50] and developing countries [6,9,10,[51][52][53][54][55], with varying degrees of participation shaped by context-specific paradigms.…”
Section: Introductionmentioning
confidence: 99%